Single-Paper Meta-Analysis: Benefits for Study Summary, Theory Testing, and Replicability - McShane, Blakeley B; Böckenholt, Ulf (Journal of Consumer Research, 2017)
Abstract A typical behavioral research paper features multiple studies of a common phenomenon that are analyzed solely in isolation. Because the studies are of a common phenomenon, this practice is inefficient and forgoes important benefits that can be obtained only by analyzing them jointly in a single-paper meta-analysis (SPM). To facilitate SPM, we introduce meta-analytic methodology that is user-friendly, widely applicable, and specially tailored to the SPM of the set of studies that appear in a typical behavioral research paper. Our SPM methodology provides important benefits for study summary, theory testing, and replicability that we illustrate via three case studies that include papers recently published in the Journal of Consumer Research and the Journal of Marketing Research. We advocate that authors of typical behavioral research papers use it to supplement the single-study analyses that independently examine the multiple studies in the body of their papers as well as the “qualitative meta-analysis” that verbally synthesizes the studies in the general discussion of their papers. When used as such, this requires only a minor modification of current practice. We provide an easy-to-use website that implements our SPM methodology.